IS THERE A SECOND CHANCE TO ASYLUM IN ROMANIA IF THE CRIMINAL CHARGE RISK ALLEGED WITHIN FIRST SET OF PROCEEDINGS DENYING THE ASYLUM CAN BE SUBSTANTIATED? - Liviu-Alexandru Viorel, (PEOPLE: International Journal of Social Sciences, 2025)
Structured on the Q&A model, the present study aims at analyzing several key legal issues stemming from the procedure of granting access to a new asylum procedure based on a criminal charge letter issued by prosecuting agent from country-of-origin existent but not known by the asylum seeker at the material time of first round of proceedings, seen as a “new element” within the meaning of Romanian Law on asylum, accompanied by a legal opinion on the legal consequences of such. Requirements for accessing a new asylum procedure in five European jurisdictions are analized and compared. Following the overview of the legal framework from Romania, 6 questions are raised: (i) is there a difference between „new elements” and „new reasons”? (ii) is it compulsory for the asylum seeker to not raise the criminal charge issue during the first asylum procedure? (iii) is the asylum seeker entitled to a second procedure if the criminal charge existed before the first round of procedures? (iv) would aggravating of punishment reasons be analized for the purpose of opening access to a second asylum procedure? (v) can the authenticity of the “new element” be called into question? (vi) is personal situation and professional trajectory relevant for getting access to a second asylum procedure? Each question receives a reasoned answer according to the law, the Romanian case-law and the legal experience of the author. The article naturally ends with specific conclusions calibrated to Romanian law particularities.